Нестационарное деформирование многослойных упругих тел в форме прямоугольного параллелепипеда - Янютин, Е. Г.; Светличная, С. Д.; Томилка, Н. Н. (НТУ "ХПИ", 2003)
The unsteady déformation of multilayered elastic solids in the shape of rectangular parallelepiped is investigated using the dynamic theory of elasticity. Motion equations and systems of primary, boundary and contact conditions are satisfied exactly owing to this method
Keywords: многослойные конструкции; волновые уравнения; динамическая теория упругости